An Enquiry into the Reasons for Lack of Participation in Learning among Individual Adult Learners: A Case Study of India - Singai, Chetan B (EDUCARE, 2010)
ABSTRACT: Poverty has become one of the major reasons for lack of motivation for participating in learning processes, especially among the adults. Poverty has victimized many individuals to leave their education and opt for employment to sustain themselves and their family. Lifelong learning as a process of learning can be of some relevance as a tool of motivation and participation in the learning among the individuals, where the individuals can be active in the labor market (enhancing motivation) and also participate in the learning process. The paper investigates the impact of poverty on lack of motivation to participate in education. The paper analyses the research problem by discussing the case of India, where two adult learners where interviewed. According to Maslowâs Hierarchy of Needs Model and Cross â Chain of Response Model provide as the theoretical perspective for the study to examine the issue of lack of motivation and participation among adult learners. The paper concludes by emphasizing on the fact that poverty does influence the adult leanerâs in India in terms of motivating them to participate in their education. This is able to be also argued that learning process involves need for motivation and participation unlike the traditional process of intellectual development. Emotion (motivation) and sociality (participation) are very important elements for enhancing cognitive abilities (formal qualification) of an individual.KEY WORDS: motivation, participation, poverty, learning, barriers for learning, and case of India.Â About the Author: Chetan B. Singai is Erasmus Mundus Masters in Lifelong Learning for Policy and Management, Danish School of Education, University of Aarhus, Denmark. He can be reached at: chetanbsingai@gmail.com and www.chetanbsingai.blogspot.comHow to cite this article? Singai, Chetan B. (2010). âAn Enquiry into the Reasons for Lack of Participation in Learning among Individual Adult Learners: A Case Study of Indiaâ in EDUCARE: International Journal for Educational Studies, Vol.2(2) February, pp.141-152. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 29, 2009); Revised (January 19, 2010); and Published (February 17, 2010).